Adult and pediatric medulloblastomas are genetically distinct and require different algorithms for molecular risk stratification - Korshunov, Andrey; Remke, Marc; Werft, Wiebke; Benner, Axel; Ryzhova, Marina; Witt, Hendrik; Sturm, Dominik; Wittmann, Andrea; Schöttler, Anna; Felsberg, Jörg; Reifenberger, Guido; Rutkowski, Stefan; et al. (Journal of clinical oncology, 2010)
Medulloblastoma (MB) is the most common malignant brain tumor in children, whereas it rarely presents in adults. We aimed to identify genetic aberrations in 146 adult MBs to evaluate age-dependent differences in tumor biology and adapt age-specific risk stratification models.
Gesehen am 22.03.2023